Use of Portable Fluorescence Spectroscopy and SIMCA Method to Test The Authenticity of Apis mellifera Honey From Coffee Flower Nectar Mixed With Two Artificial Sweeteners - Sapto Kuncoro; Diding Suhandy; Warji Warji; Dicky Ervandi (The University of Lampung, 2023)
Honey with coffee flowers nectar is native honey formed from flower nectar. In this investigation, corn syrup and rice syrup, two artificial sweeteners, were utilized as an adulterant. Portable fluorescence spectroscopy and the SIMCA method are the tools and techniques employed. There were up to 20 samples of pure Apis mellifera honey and up to 120 samples of mixed honey (MC), each used twice. Data on the emission spectra, which are excited at a wavelength of 365 nm, were measured over the wavelength range of 300-800 nm. To improve accuracy, sensitivity, and specificity, the original spectral data was altered using a number of pre-treatments. Pretreatment with the original data with smoothing moving average may accurately identify samples and provides 100% accuracy, sensitivity, and specificity. One of the steps of the SIMCA approach, the cumulative PC, has a value of 92%, which indicates that it well explains the variation of the data. The x-loading plot's values are near the peak of the waves at 378 and 460 nm, indicating the existence of phenolic and flavonoid chemicals at those wavelengths. Keywords: Apis mellifera honey, Corn syrup, Rice syrup, Portable Spectroscopy, SIMCA.